A Cross-Sectional Voxel-Based Morphometric Study of Age- and Sex-Related Changes in Gray Matter Volume in the Normal Aging Brain. Issue 2 (March 2016) - Peng, Fei; Wang, Lixin; Geng, Zuojun; Zhu, Qingfeng; Song, Zhenhu
Abstract : Objective: The aim of the study was to carry out a cross-sectional study of 124 cognitively normal Chinese adults using the voxel-based morphometry approach to delineate age-related changes in the gray matter volume of regions of interest (ROI) in the brain and further analyze their correlation with age. Methods: One hundred twenty-four cognitively normal adults were divided into the young age group, the middle age group, and the old age group. Conventional magnetic resonance imaging was performed with the Achieva 3.0 T system. Structural images were processed using VBM8 and SPM8. Regions of interest were obtained by WFU PickAtlas and all realigned images were spatially normalized. Results: Females showed significantly greater total gray matter volume than males ( t = 4.81, P = 0.0000, false discovery rate corrected). Compared with young subjects, old-aged subjects showed extensive reduction in gray matter volumes in all ROIs examined except the occipital lobe. In young- and middle-aged subjects, female and male subjects showed significant difference in the right middle temporal gyrus, right superior temporal gyrus, left angular gyrus, right middle occipital lobe, left middle cingulate gyrus, and the pars triangularis of the right inferior frontal gyrus, suggesting an interaction between age and sex ( P < 0.001, uncorrected). Logistic regression analysis revealed linear negative correlation between the total gray matter volume and age ( R 2 = 0.529, P < 0.001). Conclusions: Significant age-related differences are present in gray matter volume across multiple brain regions during aging. The VPM approach may provide an emerging paradigm in the normal aging brain that may help differentiate underlying normal neurobiological aging changes of specific brain regions from neurodegenerative impairments.